2017
DOI: 10.11648/j.ijvetr.20170306.11
|View full text |Cite
|
Sign up to set email alerts
|

The Gap Between Educational System and Job Market in International Business Law: A Model of Specialization for Solving the Problem

Abstract: Abstract:One of the aims of higher education is obtaining advanced skills and specialty, and thereby offering better job opportunities after graduation. Examining the current educational system of Master level in Iran, we came to the conclusion that there is a lack of practice on necessary specialization in the domain of International Business Law. The train Master students receive is not directed towards their future profession, which leads to their being unable to have a good performance. In order to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The authors also observed that TIVET offers suitable interpersonal skills, sufficient competency in organisational, occupational health and safety, and basic accounting skills. Where academic instruction is not profession-based, findings show that students may excel in theory but fail in practical work [56]. This position influences employability of graduates because they do not meet the employer's expectation.…”
Section: Training Needs Analysismentioning
confidence: 98%
See 3 more Smart Citations
“…The authors also observed that TIVET offers suitable interpersonal skills, sufficient competency in organisational, occupational health and safety, and basic accounting skills. Where academic instruction is not profession-based, findings show that students may excel in theory but fail in practical work [56]. This position influences employability of graduates because they do not meet the employer's expectation.…”
Section: Training Needs Analysismentioning
confidence: 98%
“…The level of theoretical knowledge exhibited by TIVET graduates have been acknowledged by employers as being satisfactory. The theory was not, however, matched by the practical know-how requisite at the workplace [56,57,39]. The authors also observed that TIVET offers suitable interpersonal skills, sufficient competency in organisational, occupational health and safety, and basic accounting skills.…”
Section: Training Needs Analysismentioning
confidence: 99%
See 2 more Smart Citations